Recrystallization processes in screen-printed CdS films - Klad’ko, V.P.; Lytvyn, O.S.; Lytvyn, P.M.; Osipenok, N.M.; Pekar, G.S.; Prokopenko, I.V.; Singaevsky, A.F.; Korchevoy, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Kinetics of recrystallization in screen-printed polycrystalline CdS films has been investigated by X-ray structure analysis and optical microscopy. The relation between the crystallite size, crystallite orientation and the macrostrain, as well as their dependence on heat treatment regimes is established. It is shown that single-phase CdS films having a thickness of some tens microns, large grain size and low residual strain can be produced at optimum technological regimes. The films obtained are suitable for fabrication of CdS/CdTe solar cells.